Localized climatisation of perishable products - Solutions for increasing energy efficiency - Wagner, J.; Schäfer, M.; Phan, L.; Schlüter, A.; Hesselbach, J.; Rosano, Michele; Lin, C. (2014)
Many industries have significant requirements regarding temperature control, air humidity and air pollution which must be strictly adhered to avoid bacterial formation and contamination. High refrigeration specifications are only required in certain areas. However, these specifications are often applied across the whole production hall which results in unnecessarily high energy demand and usage. A more energy efficient approach is the localized cooling of the product, which conditions the direct environment of the product only. This leads to the consideration of separating or localizing the products specifically requiring refrigeration in the production hall. In this paper, localized product cooling systems are analyzed in order to identify the savings potential associated with a localized refrigeration system. The study shows the energy savings potential for a manufacturing company located in three different locations: in Germany, Canada and the USA.